TANGGUNG JAWAB HUKUM TENAGA KESEHATAN TERHADAP PELANGGARAN INFORMED CONSENT DALAM PELAYANAN MEDIS - Gunawan Widjaja; Hotmaria Hertawaty Sijabat (CV. ADIBA AISHA AMIRA, 2026)
This study aims to analyse the legal liability of healthcare professionals for breaches of informed consent in medical practice through a literature review. Informed consent is a legal and ethical foundation that must be applied prior to any medical procedure, in accordance with Article 293(1) of Law No. 17 of 2023 on Health and Minister of Health Regulation No. 290/Menkes/Per/III/2008. The results of the study indicate that breaches of informed consent can occur in three main forms: failure to provide information, provision of incomplete or misleading information, and obtaining invalid consent. The legal liability of healthcare professionals encompasses four forms: civil liability under Article 1365 of the Civil Code for unlawful acts; criminal liability under Articles 359 and 351 of the Criminal Code; administrative liability in the form of sanctions ranging from a reprimand to the revocation of a practising licence; and professional disciplinary liability under the Indonesian Medical Council (MKDKI). Hospitals, as corporations, are liable under the doctrines of strict liability and vicarious liability in accordance with Article 1367 of the Civil Code and Article 46 of the Hospitals Act. This study recommends strengthening regulations, improving healthcare professionals’ communication skills, and raising awareness of patients’ rights to prevent future breaches of informed consent.